Indirect fiscal effects of long-term care insurance - Johannes Geyer; Peter Haan; Thorben Korfhage (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Informal care by close family members is the main pillar of most longterm care systems. However, due to demographic ageing the need for long-term care is expected to increase while the informal care potential is expected to decline. From a budgetary perspective, informal care is often viewed as a cost-saving alternative to subsidized formal care. This view, however neglects that many family carers are of working age and face the difficulty to reconcile care and paid work which might entail sizable indirect fiscal effects related to forgone tax revenues, lower social security contributions and higher transfer payments. In this paper we use a structural model of labor supply and the choice of care arrangement to quantify these indirect fiscal effects of informal care. Moreover based on the model we discuss the fiscal effects related to non-take up of formal care.
Keywords: J22; H31; I13; 330; labor supply; long-term care; long-term care insurance; structural model